New mesogenic materials bearing 1, 2, 4-oxadiazole moiety: Synthesis, characterization and investigation their mesomorphic behaviors. Issue 2 (3rd April 2018) - Ali, Ghassan Q.; Tomi, Ivan Hameed R.
ABSTRACT: In this work, two series containing a 1, 2, 4-oxadiazole ring as a central core were synthesized and characterized by common spectroscopic techniques, including FT-IR, 1 H-NMR, and elemental analysis. The first series was 3-(4-alkoxyphenyl)-5-(p-methylphenyl)-1, 2, 4-oxadiazole (Cn ), which consisted of alkoxy group in the terminal arm and a methyl group in the other, while, the oxidation reaction of methyl group in a series (Cn ) to the carboxy group was the method used to synthesize the second series in this work, 4-(3-(4-alkoxyphenyl)-1, 2, 4-oxadiazol-5-yl)benzoic acid (Dn ). The mesophase behaviors of these two series were studied by optical polarized microscopy (OPM) and differential scanning calorimetry (DSC). The liquid crystalline investigations of the compounds (Cn and Dn ) show that the last six homologeus of the series (Cn ), (C6 –C11 ), have a monotropic nematic phase, while only the intermediate compounds in the series (Dn ), (D3 –D9 ), displayed monotropic nematic phase, also, the liquid crystalline properties in the first and last two compounds in this series (D1, D2, D10, and D11 ) had disappeared. The differences in liquid crystalline properties between the two series, (Cn and Dn ), were discussed through the influences of the different terminal groups (–CH3 and –COOH) in addition to the effect of the 1, 2, 4-oxadiazole ring and the length of the terminal alkyl chain.